MAKASSAR ORAL POETRY VOCABULARY FOR HUMAN CATEGORY: A STUDY OF MICROSTRUCTURE IN VANDIJK CRITICAL DISCOURSE ANALYSIS - Muhammad Ali (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
This research is descriptive-qualitative which aims to describe how the vocabulary of Makassar oral poetry in Human category. The researcher is key instrument in this research. Researchers try to interpret carefully through experience as a native speaker. The data analysis technique was carried out through 3 (three) cycles, namely data collection, data reduction, and drawing conclusions and verification. Theory of VanDijk is a theoretical framework and hermeneutics as grand theory and analytical knife. Based on the results of the analysis, it shows that there are several vocabularies that are included in Human category, namely everything related to (1) the human body, (2) human physical activities, (3) human intellectual activity, (4) human nature or character. All vocabularies “human”in the poem describe the existence of Makassar people in their local and universal lives. The four human categories contained several messages, namely love for God, love for parents, the struggle of a mother, implement God’s commands and avoid his prohibitions, not giving up easily, being loyal to lovers, simple, views of life, manners, tolerance, humility, and so on. This research provides very important benefits for Indonesian and Local Language and Literature teachers in developing their learning materials in the classroom, especially in learning the appreciation of poetry and prose of local culture in each region or country.